Risk Assessment on Pressure Relief Device Using Risk Based Inspection (RBI) Method Based on API RP 581 in PT Z - Mohamad Fajar Natawijaya; Khusnun Widiyati (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
This research is about conducting a risk assessment of the pressure relief device unit by conducting a risk-based inspection analysis method. With the aim of mapping the risk categories in the PRD unit and providing recommendations for actions that must be taken to mitigate these risks with a quantitative approach. Pressure relief device (PRD) is a device that automatically discharges a certain pressure which is controlled by upstream static pressure coming from the valve and opens naturally with an increase in pressure above the opening pressure. The risk-based inspection method is carried out to calculate the risk value on an equipment by conducting analysis and calculations to determine the probability and consequence values on the PRD unit, the data used to calculate the risk value in the form of PRD data sheets include: general data, process condition data, data materials, data connection, and database and selection data, as well as inspection history records at the PRD unit (17 – PSV – 298) which are used to determine risk values, inspection plans, and recommendations for actions to be taken in mitigating risks. According to the calculation of the risk value on the PRD unit equipment (17 – PSV – 298) which was analyzed using the risk-based inspection method, the risk value for the PRD unit was 0.1135 m2/year, so it can be determined that the risk category is the medium category according to plotting against the risk matrix. The PRD unit (17 – PSV – 298) will approach the risk target as determined by the company in the 24th year since the first risk assessment was carried out using the RBI method and estimated on January 11, 2042. Based on the inspection history, there has been a leak in the PRD unit (17 – PSV – 298) during the pop test. Thus, the recommended type of inspection is the type of shop inspection/overhauls and is carried out periodically at least every 4 years. This is in accordance with PERMEN ESDM No. 32 of 2021 Article 21 Paragraph 4a.